Flexible display laminate and flexible display
The laminate for flexible displays, featuring an adhesive layer with a controlled surface free energy and specific monomer composition, addresses the issues of displacement, protrusion, and foaming in conventional adhesive layers, ensuring excellent flexibility, adhesion, and visibility even with high-polarity substrates.
Patent Information
- Application Number
- JP2024205660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-04-10
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-18
AI Technical Summary
Conventional adhesive layers in flexible displays suffer from displacement, protrusion, and foaming when repeatedly bent or bent at high speed, especially when used with high-polarity substrates like colorless polyimide, leading to display defects and reduced visibility.
A laminate for flexible displays is developed, featuring an adhesive layer with a polar term component of surface free energy calculated using the OWRK method, ranging from 0.5 mN/m or less, and a mass per unit area of 10 to 100 g/m². The adhesive layer is formed from an acrylic copolymer with specific monomer ratios and a low-polar additive, ensuring excellent flexibility and adhesion without protrusion or foaming.
The laminate effectively prevents displacement and protrusion of the adhesive layer during repeated bending or high-speed bending, maintains excellent visibility by avoiding display defects, and ensures reliable adhesion even with high-polarity substrates.
Smart Images

Figure 2025037935000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate for a flexible display including a light-transmitting flexible substrate and a pressure-sensitive adhesive layer, the laminate including a light-transmitting flexible substrate, a pressure-sensitive adhesive layer, and a polarizing plate in this order, and a laminate including the pressure-sensitive adhesive layer. The laminate can be used in a flexible display.
[0002] In recent years, input devices that combine image display devices such as liquid crystal displays (LCDs) and organic electroluminescence (OLED) displays (OLEDs) with touch panels have become widespread. Transparent conductive films used in touch panels are laminated to members such as supporting glass via an adhesive layer. Polarizing plate films used in image devices are attached to liquid crystal modules or OLED modules via an adhesive layer.
[0003] Flat displays using glass substrates have been mainstream as the image display devices, but in recent years, flexible displays such as foldable displays and rollable displays using flexible substrates such as plastics have been developed. Such flexible displays have various advantages, such as being lighter, thinner, more flexible, and more attractive in design, compared to flat displays using conventional glass substrates.
[0004] To be used in a foldable display, the material must be able to withstand bending of the display (flexibility). In general, the material must have dynamic flexibility, which means that it does not foam, float, or peel when repeatedly bent.
[0005] In order to solve these problems, Patent Document 1 discloses a pressure-sensitive adhesive layer that contains a resin syrup produced by partially polymerizing a (meth)acrylate monomer and a photoinitiator, and has a storage modulus of 1.0 × 10 at 25°C and 1 Hz. 6 ~1.0×107 Patent Document 2 discloses an optically transparent adhesive sheet having a viscosity of 1000 psig (Pa). Patent Document 2 also discloses an adhesive layer formed of an adhesive containing a base polymer, a photocurable compound, and a photoinitiator. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2020-517800 A [Patent Document 2] JP 2020-097737 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, with such conventional adhesive layers, when repeatedly bent by a flexible display, the adherends bonded together by the adhesive layer may become misaligned, or the adhesive layer protruding from the edges may come into contact with surrounding components, resulting in poor foldability, and the bendability of the adhesive layer is not sufficient. Furthermore, in recent years, colorless polyimide, which is a transparent polyimide having overwhelming mechanical properties, has been used as a light-transmitting flexible substrate for foldable displays. This has resulted in a more stringent requirement for the durability of the adhesive layer, but when a laminate in which an adhesive layer and a colorless polyimide are bonded is repeatedly bent, there is a problem that the adhesive layer may lift at the bent portion, causing misalignment between the adherends, or foaming may occur in the adhesive layer, causing whitening due to air bubbles. In addition, even for products that were found to be problem-free in normal repeated bending tests, there are problems with display problems when the products are bent at a higher speed than expected, such as misalignment between the adherends, lifting of the adhesive layer, and foaming in the adhesive layer.
[0008] Therefore, the present disclosure aims to provide a laminate in which the bonded adherends do not shift from each other even when repeatedly bent or bent at high speed, and the adhesive layer does not protrude from the edge.Furthermore, the present disclosure aims to provide a laminate for flexible displays in which display defects do not occur at bent parts even when a highly polar substrate such as a colorless polyimide is used as the light-transmitting flexible substrate, and a flexible display with excellent visibility. [Means for solving the problem]
[0009] As a result of extensive investigations, the present inventors have found that the problems can be solved in the following manner. That is, the present disclosure relates to a laminate for flexible displays comprising a pressure-sensitive adhesive layer on a light-transmitting flexible substrate, wherein a polar term component of surface free energy of the light-transmitting flexible substrate calculated based on the OWRK method from the contact angle of water and the contact angle of diiodomethane is 3.0 mN / m or more, a polar term component of surface free energy of the pressure-sensitive adhesive layer calculated based on the OWRK method from the contact angle of water and the contact angle of diiodomethane is 0.5 mN / m or less, and a mass per unit area of the pressure-sensitive adhesive layer is 10 to 100 g / m. 2 The present invention provides a laminate for flexible displays, characterized in that the pressure-sensitive adhesive layer is formed from an acrylic pressure-sensitive adhesive, the acrylic pressure-sensitive adhesive comprising an acrylic copolymer containing, based on 100 mass% of the acrylic copolymer, 25 mass% or less of repeating units derived from hydroxyl group-containing monomers, 10 mass% or less of repeating units derived from acid-containing monomers, 15 mass% or less of repeating units derived from amide group-containing monomers, 15 mass% or less of repeating units derived from amino group-containing monomers, and 75 to 90 mass% of repeating units derived from (meth)acrylic acid alkyl esters having an alkyl group with 4 or more carbon atoms, and a low-polarity additive. Effect of the Invention
[0010] The present disclosure makes it possible to provide a laminate in which the bonded adherends do not shift from each other even when repeatedly bent or bent at high speed, and the adhesive layer does not protrude from the edge. Furthermore, even when a highly polar substrate such as colorless polyimide is used as the light-transmitting flexible substrate, it is possible to provide a laminate for flexible displays in which display defects do not occur at bent portions, and a flexible display with excellent visibility. Furthermore, by using the laminate of the present disclosure, a flexible display with excellent visibility can be provided. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic cross-sectional view partially illustrating a laminate according to an embodiment of the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view partially illustrating a flexible display, which is an example of the use of a laminate according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, configuration examples of the laminate and flexible display of the present disclosure will be described, but the present disclosure is not limited thereto. In addition, in this specification, a numerical range specified by "~" includes the numerical values written before and after "~" as the range of the lower and upper limits. Furthermore, "film" and "sheet" are not distinguished by thickness. In other words, in this specification, a "sheet" includes a thin film-like material, and a "film" includes a thick sheet-like material. The term "adherend" refers to the object to which the adhesive layer of the adhesive sheet is attached. For example, in the case of a laminate for a flexible display having, in that order, a light-transmitting flexible substrate, an adhesive layer, and a polarizing plate, the term refers to the light-transmitting flexible substrate and the polarizing plate. Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a combination of two or more types.
[0013] <Adhesive layer for flexible displays> The pressure-sensitive adhesive layer used in the laminate of the present disclosure is characterized in that the polar term component of the surface free energy calculated based on the OWRK method from the contact angle of water and the contact angle of diiodomethane is 0.5 mN / m or less. As a result, even if the laminated substrate is repeatedly bent or bent at high speed, the laminated substrate does not shift, and the adhesive layer does not protrude from the edge. Furthermore, even if a highly polar substrate such as colorless polyimide is used as the light-transmitting flexible substrate, no display defects occur at the bent portion.
[0014] <Polar term component of surface free energy> The polar term component of the surface free energy is 0.5 mN / m or less. The smaller the polar term component of the surface free energy of the adhesive layer, the more preferable, and it is preferably 0 mN / m or more. In addition, it is preferably 0.3 mN / m or less, and more preferably 0.2 mN / m or less. By adjusting the polar term component to 0.5 mN / m or less, an adhesive layer can be obtained in which the bent portion does not whiten even when repeatedly bent or bent at high speed, and the adherends that are bonded together do not slip. Although the mechanism by which such an effect is obtained is unclear, it is presumed that this is because, even if the adhesive layer exhibits strong adhesion to the adherend, the strong intermolecular attractive force due to the dipole interaction does not contribute to the expression of the adhesive force, so that when a shear force is applied by bending, the adhesive layer follows the adherend without peeling off.
[0015] The polar term component of the surface free energy can be controlled to 0.5 mN / m or less by reducing the polarity of the resin used in the adhesive and by incorporating a low-polarity additive that is concentrated on the surface after coating.
[0016] The surface free energy is calculated based on the OWRK method from the contact angle of water and the contact angle of diiodomethane at 25°C. Specifically, the contact angle of each liquid is measured 1 second after the droplet lands on the surface with a volume of 1 μl. The device used to measure the contact angle is not particularly limited, but may be, for example, an automatic contact angle meter DM-501Hi manufactured by Kyowa Interface Science Co., Ltd. The polar term component of the surface free energy is calculated together with the dispersion term component by the OWRK method.
[0017] <Gel fraction> The pressure-sensitive adhesive layer of the present disclosure preferably has a gel fraction of 55 to 90% by mass, more preferably 60 to 80% by mass. When the gel fraction is 55% by mass or more, the cohesive strength of the pressure-sensitive adhesive is improved, a strong pressure-sensitive adhesive layer is obtained, and the pressure-sensitive adhesive layer is less likely to protrude from the edge when folded. When the gel fraction is 90% by mass or less, the stress relaxation property of the pressure-sensitive adhesive is improved, a flexible pressure-sensitive adhesive layer is easily obtained, the adhesion is improved, and the misalignment of adherends when folded can be more effectively suppressed.
[0018] [Gel fraction measurement method] The gel fraction can be determined as the amount of insoluble matter in a solvent such as ethyl acetate. Specifically, as represented by the following formula 1, the gel fraction is determined as the mass fraction (unit: mass%) of the insoluble matter after the pressure-sensitive adhesive layer is immersed in ethyl acetate at 50° C. for one day relative to the pressure-sensitive adhesive layer before immersion. (Formula 1) Gel fraction (mass%) = (Y / X) x 100 X = mass of adhesive layer before immersion (g) Y = mass of adhesive layer after immersion (g) In general, the gel fraction of a polymer is equal to the degree of crosslinking, and the more crosslinked parts in the polymer, the higher the gel fraction. The gel fraction (amount of crosslinked structure introduced) can be adjusted to a desired range by the method of introducing the crosslinked structure, the type and amount of the crosslinking agent, etc.
[0019] <Adhesive> The pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive. The resin type of the adhesive is an acrylic adhesive. By using an acrylic adhesive, it becomes easier to balance various performances while adjusting the polar term component of the surface free energy to 0.5 mN / m or less.
[0020] [Acrylic adhesive] The acrylic adhesive is mainly composed of an acrylic copolymer, which is a (meth)acrylic acid ester polymer, and contains a low-polarity additive described later, and may contain a curing agent and other additives as necessary. The (meth)acrylic acid ester includes an acrylic acid ester and a methacrylic acid ester. The monomer is a monomer having an ethylenically unsaturated group.
[0021] (Acrylic copolymer) The acrylic copolymer is a polymer of a monomer containing one or more kinds of acrylic monomers such as (meth)acrylic acid alkyl esters. Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isoamyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, and (meth)acrylic acid alkyl esters. Examples of the acrylates include those having a straight-chain or branched alkyl group, such as n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, methoxyethyl (meth)acrylate, and ethoxyethyl (meth)acrylate, as well as those having a cyclic alkyl group, such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate.
[0022] The acrylic copolymer is preferably copolymerized with a monomer containing a unit derived from a (meth)acrylic acid (ester) having a functional group. The inclusion of the functional group can impart cohesive strength to the adhesive layer, and the use of a curing agent in the adhesive can further improve the cohesive strength of the adhesive layer, making it easier to prevent the adhesive from protruding when bent.
[0023] The functional group of the (meth)acrylic acid (ester) having a functional group is preferably at least one selected from a carboxyl group, a hydroxyl group, an amino group, an amide group, an oxyalkylene group, an epoxy group, and an isocyanate group, more preferably at least one selected from a carboxyl group, a hydroxyl group, an amino group, and an amide group, and further preferably at least one selected from a carboxyl group and a hydroxyl group, or both. Examples of the monomer unit having a carboxyl group (or an acid-containing monomer unit) include acrylic acid and methacrylic acid. The monomer unit having a hydroxyl group is a repeating unit derived from a monomer having a hydroxyl group. Examples of the monomer having a hydroxyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate, (meth)acrylic acid [(mono-, di-, or poly)alkylene glycol] such as mono(diethylene glycol) (meth)acrylate, and (meth)acrylic acid lactones such as monocaprolactone (meth)acrylate. Examples of the monomer unit having an amino group include repeating units derived from primary amino group-containing monomers such as aminomethyl(meth)acrylate and aminoethyl(meth)acrylate; secondary amino group-containing monomers such as t-butylaminoethyl(meth)acrylate; tertiary amino group-containing monomers such as ethylaminoethyl(meth)acrylate, dimethylaminoethyl(meth)acrylate and diethylaminoethyl(meth)acrylate; and monomers having an amino group such as allylamine, vinylpyridine, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole and vinyloxazole. Examples of monomer units having an amide group include (meth)acrylamide, N-vinyl lactams, cyclic amides such as vinyl morpholine and (meth)acryloyl morpholine, N-vinyl carboxylic acid amides such as N-vinyl formamide and N-vinyl acetamide, acrylamide, N,N-dimethyl acrylamide, etc. N-vinyl lactams are monomers having a cyclic lactam ring, and examples thereof include N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-ε-caprolactam, and compounds having a structure in which one or more of the hydrogen atoms of these are substituted with a substituent. Examples of the substituent include an alkyl group having 1 to 20 carbon atoms, an alkyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a carboxy ester group having 3 to 20 carbon atoms, and an amino group having 1 to 20 carbon atoms, but do not include acidic groups such as a hydroxyl group, a carboxylic acid (salt) group, a sulfonic acid (salt) group, or a hypophosphorous acid (salt) group. Examples of monomer units having an oxyalkylene group include methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol #400 (meth)acrylate, methoxydipropylene glycol (meth)acrylate, methoxytripropylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, ethyl carbitol (meth)acrylate, 2-ethylhexyl carbitol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenoxydiethylene glycol (meth)acrylate. Examples of the monomer unit having an isocyanate group include 2-isocyanate ethyl (meth)acrylate, 3-isocyanate propyl (meth)acrylate, and 4-isocyanate butyl (meth)acrylate. Examples of the monomer unit having an epoxy group include repeating units derived from a monomer having a glycidyl group, such as glycidyl (meth)acrylate.
[0024] The hydroxyl group-containing monomer is 25% by mass or less, more preferably 20% by mass or less, in 100% by mass of the acrylic copolymer. In the present disclosure, when a certain monomer is n% by mass (or is contained in n% by mass) in 100% by mass of the acrylic copolymer, it means that the repeating unit derived from that monomer accounts for n% by mass of the copolymer. In addition, when a certain monomer is n% by mass or less (or is contained in n% by mass or less) in 100% by mass of the acrylic copolymer, it may also include an embodiment in which the monomer is 0% by mass. The amount of the acid-containing monomer is preferably 10% by mass or less, more preferably 7% by mass or less, based on 100% by mass of the acrylic copolymer. The amide group-containing monomer is contained in 100% by mass of the acrylic copolymer, preferably 15% by mass or less, more preferably 10% by mass or less, and most preferably 7% by mass or less. The amino group-containing monomer is contained in the acrylic copolymer in an amount of 15% by mass or less, more preferably 10% by mass or less, and most preferably 7% by mass or less, based on 100% by mass of the acrylic copolymer. The ratio of the oxyalkylene group-containing monomer is preferably 30% by mass or less, more preferably 15% by mass or less, and most preferably 12% by mass or less. Other monomers copolymerizable with acrylic monomers are preferably 20% by mass or less, more preferably 15% by mass or less, and most preferably 12% by mass or less, for monomers having a water / octanol partition coefficient log Kow of 2.22 or less at 25°C and monomers that are arbitrarily miscible with water. Each of the monomers described above in this paragraph may be 0% by mass or more (i.e., may be 0% by mass) in 100% by mass of the acrylic copolymer. For example, in 100% by mass of the acrylic copolymer, the hydroxyl group-containing monomer may be 0.5% by mass or more, and the acid-containing monomer may be 0.2% by mass or more. In one embodiment, in 100% by mass of the acrylic copolymer, the hydroxyl group-containing monomer may be 0.5% by mass or more, the acid-containing monomer may be 0.2% by mass or more, and each of the other monomers described above in this paragraph may be 0% by mass or more. The (meth)acrylic acid alkyl ester having an alkyl group with 4 or more carbon atoms accounts for 75 to 90 mass % of 100 mass % of the acrylic copolymer, and preferably 78 to 88 mass %. By using this type of monomer as the main component, the polarity of the acrylic copolymer is reduced. The number of carbon atoms in the alkyl group is typically 16 or less.
[0025] The (meth)acrylic copolymer may have other monomer units in addition to the above-mentioned monomer units, if necessary. The other monomers may be any monomers that can be copolymerized with the above-mentioned acrylic monomers, and examples thereof include vinyl carboxylate esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl cyclohexane carboxylate, and vinyl benzoate, and styrene. Among these, vinyl acetate, vinyl propionate, and vinyl butyrate are hydrophilic with a water / octanol partition coefficient log Kow of 2.30 or less at 25°C, so in order to reduce the polarity of the acrylic copolymer, it is preferable to reduce the ratio as described below. The log Kow value can be calculated, for example, based on the structural formula of the monomer using software called HSPiP (Steven Abbott, Hiroshi Yamamoto).
[0026] (Production of acrylic copolymer) The acrylic copolymer can be produced by polymerizing a monomer mixture. The polymerization can be carried out by a known polymerization method such as solution polymerization, bulk polymerization, emulsion polymerization, suspension polymerization, etc., but solution polymerization is preferred. The solvent used in the solution polymerization is preferably, for example, acetone, methyl acetate, ethyl acetate, toluene, xylene, anisole, methyl ethyl ketone, cyclohexanone, etc. The polymerization temperature is preferably a boiling point reaction at 60 to 120° C. The polymerization time is preferably about 5 to 12 hours.
[0027] The polymerization initiator used in the polymerization is preferably a radical polymerization initiator, and the radical polymerization initiator is generally a peroxide or an azo compound. Examples of peroxides include dialkyl peroxides such as di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, and 2,5-di(t-butylperoxy)hexyne-3; Peroxyesters such as t-butyl peroxybenzoate, t-butyl peroxyacetate, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane; ketone peroxides such as cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide; Peroxyketals such as 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, and n-butyl-4,4-bis(t-butylperoxy)valerate; Hydroperoxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, and 2,5-dimethylcyclohexane-2,5-dihydroperoxide; diacyl peroxides such as benzoyl peroxide, decanoyl peroxide, lauroyl peroxide, and 2,4-dichlorobenzoyl peroxide; Examples include peroxydicarbonates such as bis(t-butylcyclohexyl) peroxydicarbonate.
[0028] Examples of the azo compound include 2,2'-azobisbutyronitrile such as 2,2'-azobisisobutyronitrile (ABN) and 2,2'-azobis(2-methylbutyronitrile); 2,2'-azobisvaleronitriles such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile); 2,2'-azobispropionitriles such as 2,2'-azobis(2-hydroxymethylpropionitrile); Examples include 1,1'-azobis-1-alkanenitriles such as 1,1'-azobis(cyclohexane-1-carbonitrile).
[0029] The polymerization initiator is preferably used in an amount of 0.01 to 10 parts by mass, more preferably 0.1 to 2 parts by mass, based on 100 parts by mass of the monomer mixture.
[0030] (Mass average molecular weight (Mw)) The mass average molecular weight of the acrylic copolymer is preferably 800,000 to 1,800,000, and more preferably 1,000,000 to 1,500,000. If it is in the range of 800,000 to 1,800,000, the cohesive strength is improved, and the pressure-sensitive adhesive layer is less likely to protrude from the edge when folded. The mass average molecular weight is a polystyrene-equivalent value measured by gel permeation chromatography (GPC).
[0031] (hardening agent) The acrylic adhesive preferably contains a curing agent. The curing agent to be blended into the adhesive is preferably one that reacts with the functional group of the monomer having the functional group by heat or the like to form a bond. The blending of the curing agent improves the cohesive strength of the adhesive layer, and further improves durability and stain resistance.
[0032] The curing agent can be appropriately selected from known crosslinking agents such as isocyanate compounds, epoxy compounds, oxazoline compounds, aziridine compounds, carbodiimide compounds, metal chelate compounds, butylated melamine compounds, etc., taking into consideration the reactivity with the functional group of the polymer in the adhesive. For example, when the functional group of the polymer in the adhesive contains a hydroxyl group, an isocyanate compound can be used.
[0033] The isocyanate compound is an isocyanate having two or more isocyanate groups. The isocyanate compound is preferably, for example, an isocyanate monomer such as an aromatic polyisocyanate, an aliphatic polyisocyanate, an araliphatic polyisocyanate, or an alicyclic polyisocyanate, as well as a biuret, a nurate, or an adduct thereof.
[0034] Examples of aromatic polyisocyanates include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate.
[0035] Examples of aliphatic polyisocyanates include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HMDI), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0036] Examples of the aromatic aliphatic polyisocyanate include ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.
[0037] Examples of alicyclic polyisocyanates include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate (also known as IPDI, isophorone diisocyanate), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanatemethyl)cyclohexane.
[0038] The biuret form is a self-condensation product having a biuret bond formed by self-condensation of an isocyanate monomer, for example, a biuret form of hexamethylene diisocyanate.
[0039] The nurate form is a trimer of an isocyanate monomer, such as a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, or a trimer of tolylene diisocyanate.
[0040] The adduct is a bifunctional or higher isocyanate compound obtained by reacting an isocyanate monomer with a bifunctional or higher low-molecular active hydrogen-containing compound. Examples of the adduct include a compound obtained by reacting trimethylolpropane with hexamethylene diisocyanate, a compound obtained by reacting trimethylolpropane with tolylene diisocyanate, a compound obtained by reacting trimethylolpropane with xylylene diisocyanate, a compound obtained by reacting trimethylolpropane with isophorone diisocyanate, and a compound obtained by reacting 1,6-hexanediol with hexamethylene diisocyanate.
[0041] The isocyanate compound is preferably a trifunctional isocyanate compound from the viewpoint of forming a sufficient crosslinked structure. The isocyanate compound is more preferably an adduct or nurate, which is a reaction product between an isocyanate monomer and a trifunctional low molecular weight active hydrogen-containing compound. The isocyanate compound is preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a nurate of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, a nurate of tolylene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, or a nurate of isophorone diisocyanate, and more preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, or a trimethylolpropane adduct of isophorone diisocyanate.
[0042] Examples of epoxy compounds include glycerin diglycidyl ether, 1,6-hexanediol diglycidyl ether, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidylaminophenylmethane.
[0043] Examples of the aziridine compound include N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxite), tris-2,4,6-(1-aziridinyl)-1,3,5-triazine, and 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane.
[0044] The carbodiimide compound is preferably a high molecular weight polycarbodiimide produced by decarboxylation condensation of a diisocyanate compound in the presence of a carbodiimide catalyst. The commercially available high molecular weight polycarbodiimide is preferably the Carbodilite series from Nisshinbo Industries, Ltd. Among them, Carbodilite V-03, 07, and 09 are preferred because of their excellent compatibility with organic solvents.
[0045] The metal chelate is preferably a coordination compound of a polyvalent metal such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, or zirconium with acetylacetone or ethyl acetoacetate. Examples of the metal chelate include aluminum ethyl acetoacetate diisopropylate, aluminum trisacetylacetonate, aluminum bisethyl acetoacetate monoacetylacetonate, and aluminum alkyl acetoacetate diisopropylate.
[0046] The curing agent is preferably contained in an amount of 0.02 to 4.0 parts by mass, more preferably 0.04 to 1.0 parts by mass, and even more preferably 0.04 to 0.4 parts by mass, relative to 100 parts by mass of the acrylic copolymer in the adhesive. When the content is 0.02 parts by mass or more, the cohesive strength is further improved, and when it is 4 parts by mass or less, it is preferable because it becomes easier to achieve both cohesive strength and flexibility.
[0047] The acrylic pressure-sensitive adhesive may contain, in addition to the silane coupling agent and chlorinated polyolefin described below, various resins, oils, softeners, dyes, pigments, antioxidants, UV absorbers, weather stabilizers, plasticizers, fillers, antioxidants, antistatic agents, and the like as optional components, so long as the problem can be solved.
[0048] Methods for adjusting the polar term component of the adhesive layer to 0.5 mN / m or less include reducing the polarity of the resin used in the adhesive and incorporating a low-polarity additive that is unevenly distributed on the surface after coating.
[0049] For example, in order to reduce the polarity of an acrylic copolymer, the ratio of (meth)acrylic acid alkyl esters having an alkyl group with 1 to 3 carbon atoms, hydroxyl group-containing monomers, acid-containing monomers, amide group-containing monomers, amino group-containing monomers, oxyalkylene group-containing monomers, or monomers copolymerizable with these other acrylic monomers, which have a water / octanol partition coefficient log Kow of 2.22 or less at 25°C, and which are arbitrarily miscible with water, can be reduced, and the ratio of (meth)acrylic acid alkyl esters having an alkyl group with 4 or more carbon atoms can be increased.
[0050] Specifically, the (meth)acrylic acid alkyl ester having an alkyl group with 1 to 3 carbon atoms is preferably 25 mass% or less, more preferably 20 mass% or less, even more preferably 18 mass% or less, and still more preferably 15 mass% or less, based on 100 mass% of the acrylic copolymer. The amount of the hydroxyl group-containing monomer is preferably 5% by mass or less, and more preferably 2% by mass or less, based on 100% by mass of the acrylic copolymer. The amount of the acid-containing monomer is preferably 5% by mass or less, more preferably 2% by mass or less, and most preferably 1% by mass or less, based on 100% by mass of the acrylic copolymer. The amount of the amide group-containing monomer is preferably less than 5% by mass, more preferably 3% by mass or less, and most preferably 1% by mass or less, based on 100% by mass of the acrylic copolymer. The amino group-containing monomer is preferably less than 5% by mass, more preferably 3% by mass or less, and most preferably 1% by mass or less, based on 100% by mass of the acrylic copolymer. The ratio of the oxyalkylene group-containing monomer is preferably less than 20% by mass, more preferably 10% by mass or less, and most preferably 5% by mass or less. Among other monomers copolymerizable with acrylic monomers, the monomers having a water / octanol partition coefficient log Kow of 2.22 or less at 25°C and monomers that are arbitrarily miscible with water are preferably less than 10% by mass, more preferably 5% by mass or less, further preferably 3% by mass or less, and most preferably 1% by mass or less. Each of the monomers mentioned above in this paragraph may be present in an amount of 0% by weight or more (i.e., may be 0% by weight) in 100% by weight of the acrylic copolymer. The (meth)acrylic acid alkyl ester having an alkyl group with 4 or more carbon atoms preferably accounts for 80% by mass or more, and more preferably 85% by mass or more, in 100% by mass of the acrylic copolymer.
[0051] Methods for incorporating low-polarity additives that are unevenly distributed on the surface after coating include adding a silane coupling agent, a chlorinated polyolefin, or a combination thereof to the adhesive. The amount of these low-polarity additives, either alone or in total, is preferably 0.05 parts by mass or more and 0.5 parts by mass or less, and more preferably 0.1 parts by mass or more and 0.3 parts by mass or less, per 100 parts by mass of the resin component of the acrylic copolymer. In this case, the polar term component of the surface free energy of the acrylic copolymer before the incorporation of the low-polarity additive (i.e., without the addition of the low-polarity additive) is preferably 2.0 mN / m or less, and more preferably 1.5 mN / m or less.
[0052] Examples of the silane coupling agent include an alkoxysilane compound having a (meth)acryloxy group, an alkoxysilane compound having a vinyl group, an alkoxysilane compound having an amino group, an alkoxysilane compound having a mercapto group, and an alkoxysilane compound having an epoxy group. Specific examples of commercially available products include KBM403 (3-glycidoxypropyltrimethoxysilane), KBE403 (3-glycidoxypropyltriethoxysilane), KBM303 (2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane) (all manufactured by Shin-Etsu Chemical Co., Ltd.), and BYK-325N (polyether-modified polymethylalkylsiloxane) (manufactured by BYK Japan KK).
[0053] Examples of chlorinated polyolefins include chlorinated polypropylene, acid-modified chlorinated polypropylene, acrylic-modified chlorinated polypropylene, chlorinated polyethylene, and chlorinated ethylene vinyl acetate (EVA) copolymers. From the viewpoints of good compatibility with acrylic copolymers and the like and effective reduction in polarity, chlorinated polypropylene and chlorinated ethylene vinyl acetate copolymers are preferred. Specific examples of commercially available products include Superchlorine 390S (chlorinated polypropylene, chlorine content 36%) and Superchlorine BX (chlorinated EVA, chlorine content 18%) (both manufactured by Nippon Paper Industries Co., Ltd.).
[0054] <Laminate for flexible displays> The laminate for flexible displays comprises an adhesive layer on a light-transmitting flexible substrate. For example, it has a structure of substrate / adhesive layer / polarizing plate. It is preferable to provide the light-transmitting flexible substrate, adhesive layer, and polarizing plate in this order. This allows the laminate to have excellent transparency and flexibility.
[0055] An example of a schematic cross-sectional view partially illustrating a laminate according to an embodiment of the present disclosure is shown in Fig. 1. In Fig. 1, 3 is a light-transmitting flexible substrate (cover panel), 1 is a pressure-sensitive adhesive layer, and 4 is a polarizing plate.
[0056] In the laminate shown in FIG. 1, a light-transmitting flexible substrate (cover panel) is attached to a polarizing plate via an adhesive layer.
[0057] [Light-transmitting flexible base material] As the light-transmitting flexible substrate (cover panel), a transparent plastic substrate can be used. In the present disclosure, the polar term component of the surface free energy of the light-transmitting flexible substrate is 3.0 mN / m or more, preferably 4.0 mN / m or more. The adhesive layer having a polar term component of 0.5 mN / m or less and the light-transmitting flexible substrate having a polar term component of 3.0 mN / m or more do not have too strong adhesion due to the polar attraction, and the adhesive layer follows the movement of the substrate during repeated bending, making it difficult for whitening of the bent portion or misalignment of the adherends caused by the adhesive layer to occur. It is preferable to use a light-transmitting flexible substrate having a polar term component of 4.0 mN / m or more, since the effects of the present disclosure are more excellent. The upper limit of the polar term component of the surface free energy of the light-transmitting flexible substrate is not particularly limited, but it is typically 10 mN / m or less.
[0058] Examples of materials for such light-transmitting flexible substrates include acrylic resins such as polyethylene terephthalate (PET) and polymethyl methacrylate (PMMA), and plastic materials such as polycarbonate, polycycloolefin, and polyimide. In particular, PET film or polyimide is preferred, and polyimide is most preferred in terms of durability. The plastic materials can be used alone or in combination of two or more kinds.
[0059] The pressure-sensitive adhesive layer used in the laminate of the present disclosure has excellent flex resistance, and therefore, even when a colorless polyimide obtained by making polyimide transparent is used as the substrate, it is possible to obtain a laminate in which misalignment and whitening between adherends is suppressed.
[0060] As the light-transmitting flexible substrate (cover panel), among the transparent plastic substrates described above, a transparent plastic substrate having excellent heat resistance, i.e., a transparent plastic substrate in which deformation is suppressed or prevented under harsh conditions such as high temperature or high temperature and high humidity, can be preferably used.
[0061] The light-transmitting flexible substrate may be subjected to surface treatment such as plasma treatment, corona treatment, flame treatment, UV treatment, etc. Even transparent plastic substrates such as polyethylene (PE) and polypropylene (PP) that have a polar term component value of less than 3.0 mN / m when untreated can have a polar term component value of 3.0 mN / m or more by subjecting them to the above surface treatment, and can be used in the embodiments of the present disclosure.
[0062] The thickness of the light-transmitting flexible substrate is not particularly limited, and is, for example, preferably from 100 to 2000 μm, and more preferably from 200 to 1000 μm.
[0063] <Production of laminates for flexible displays> The laminate can be produced, for example, by peeling off the release film from a pressure-sensitive adhesive sheet having release films on both sides of the pressure-sensitive adhesive layer, and attaching the pressure-sensitive adhesive layer to an adherend such as a light-transmitting flexible substrate or a polarizing plate, etc. Alternatively, the pressure-sensitive adhesive layer can be directly formed on a light-transmitting flexible substrate, and then an adherend or a pressure-sensitive adhesive layer provided on another pressure-sensitive adhesive sheet can be attached to the pressure-sensitive adhesive layer to form a laminate.
[0064] [Adhesive sheet] The pressure-sensitive adhesive sheet can be produced according to a conventional production method. For example, it can be produced by a method in which a pressure-sensitive adhesive is directly applied to one side of a release film so that the thickness after drying is a predetermined thickness to form a pressure-sensitive adhesive layer, and another release film is then attached thereto, or a method in which a pressure-sensitive adhesive is applied to one side of each of two release films so that the thickness after drying is a predetermined thickness to form two pressure-sensitive adhesive layers, and then the pressure-sensitive adhesive layers are attached to each other.
[0065] When applying the pressure-sensitive adhesive, a conventional coater such as a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, bar coater, knife coater, or spray coater can be used.
[0066] The pressure-sensitive adhesive sheet may be in the form of a rolled pressure-sensitive adhesive tape by cutting the sheet to a suitable width and winding the sheet into a roll.
[0067] The thickness of the adhesive layer is not particularly limited and is, for example, preferably 10 to 500 μm, more preferably 50 to 200 μm. When the thickness of the adhesive layer is 10 to 500 μm, sufficient cohesive strength is easily obtained, there is no misalignment or protrusion of the edge of the adhesive layer, and flexibility during high-speed bending can be achieved, which is preferable.
[0068] The mass per unit area of the adhesive layer (hereinafter also referred to as the coating amount) is 10 to 100 g / m 2 25-70g / m 2 By setting the mass per unit area of the adhesive layer within this range, it is possible to obtain an adhesive layer that does not whiten at the bent portion even when repeatedly bent, and does not cause misalignment between adherends. 2 If the coating amount is 100 g / m or more, the adhesive layer will be sufficient to conform to the adherend when folded, and the occurrence of edge misalignment due to lifting can be further suppressed. 2 By satisfying this condition, it is possible to further prevent the pressure-sensitive adhesive layer from protruding from the end portion when the sheet is folded.
[0069] The release film is not particularly limited, but a transparent plastic substrate can be suitably used. Examples of the material of the transparent plastic substrate include polyester such as polyethylene terephthalate (PET), acrylic resin such as polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose, polysulfone, polyarylate, polycycloolefin, and other plastic materials. The plastic materials can be used alone or in combination of two or more kinds.
[0070] As the release film, among the transparent plastic substrates described above, a transparent plastic substrate having excellent heat resistance, i.e., a transparent plastic substrate in which deformation is suppressed or prevented under severe conditions such as high temperature or high temperature and high humidity, can be preferably used.
[0071] The release film may have either a single layer or multiple layers. The surface of the transparent substrate may be subjected to an appropriate surface treatment, for example, a physical treatment such as a corona discharge treatment or a plasma treatment, or a chemical treatment such as an undercoat treatment.
[0072] Flexible Display A flexible display preferably includes the laminate of the present disclosure and an optical element. This allows the display of the present disclosure to have excellent flexibility and visibility. For example, the optical element can be attached to the polarizing plate of the laminate via an additional adhesive layer. The optical element is not particularly limited, and examples thereof include a liquid crystal element and an organic EL element.
[0073] Fig. 2 shows an example of a schematic cross-sectional view partially illustrating a display, which is an example of the use of the pressure-sensitive adhesive sheet of the present disclosure. In Fig. 2, 3 is a light-transmitting flexible substrate (cover panel), 1 is a first pressure-sensitive adhesive layer, 4 is a polarizing plate, 5 is a second pressure-sensitive adhesive layer, 6 is a barrier layer such as silicon nitride, 7 is an organic EL layer, 8 is a support such as polyimide, and 9 is an organic EL cell. Note that the configuration of the display is not limited to that shown in Fig. 2.
[0074] In the display shown in Fig. 2, a light-transmitting flexible substrate (cover panel) is attached to a polarizing plate via the adhesive layer (first adhesive layer) of the present disclosure, and is further attached to an organic EL cell via an adhesive layer for polarizing plate (second adhesive layer). In this way, the adhesive sheet of the present disclosure can be used in a form in which a transparent adhesive layer formed from the adhesive is attached to a light-transmitting flexible substrate (cover panel) and a polarizing plate, and the laminate is further attached to an organic EL cell via an adhesive layer for polarizing plate. For example, in FIG. 2, the pressure-sensitive adhesive layer of the present disclosure can be used as either the first pressure-sensitive adhesive layer or the second pressure-sensitive adhesive layer. In general, when comparing the first pressure-sensitive adhesive layer with the second pressure-sensitive adhesive layer, the first pressure-sensitive adhesive layer is required to have higher quality, and the pressure-sensitive adhesive of the present disclosure is preferably used for the first pressure-sensitive adhesive layer because of its good adhesion and bonding to the substrate. In this case, the pressure-sensitive adhesive for forming the second pressure-sensitive adhesive layer may be the pressure-sensitive adhesive of the present disclosure or a conventionally known pressure-sensitive adhesive.
[0075] There are no particular limitations on the uses of the displays, but examples include OLED televisions, OLED smartphones, OLED tablets, and OLED smartwatches. EXAMPLES
[0076] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited thereto. In the examples, unless otherwise specified, "parts" means "parts by mass", "%" means "% by mass", and "RH" means relative humidity. In addition, the blending amounts in the tables are parts by mass. Note that blank spaces in the tables indicate that the corresponding component is not blended. The method for measuring the mass average molecular weight of the acrylic copolymer is as follows.
[0077] <Measurement of mass average molecular weight of acrylic copolymer> The mass average molecular weight (Mw) can be measured using a GPC "LC-GPC system" manufactured by Shimadzu Corporation, and can be converted using polystyrene with a known molecular weight as a standard substance. Device name: Shimadzu Corporation, LC-GPC system "Prominence" Column: Four GMHXL columns manufactured by Tosoh Corporation and one HXL-H column manufactured by Tosoh Corporation were connected together. Mobile phase solvent: Tetrahydrofuran Flow rate: 1.0ml / min Column temperature: 40℃
[0078] <Production Example of Acrylic Copolymer> (Acrylic copolymer (R9)) A reaction vessel (hereinafter simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping device, and a nitrogen inlet tube was charged with 20 parts of methyl acrylate (MA), 43.2 parts of 2-ethylhexyl acrylate (2EHA), 35 parts of dodecyl acrylate (DOA), 1 part of 4-hydroxybutyl acrylate (4HBA), 0.8 parts of acrylic acid (AA), and 0.2 parts of 2,2'-azobisisobutyronitrile (hereinafter simply referred to as "AIBN") as an initiator, and the atmosphere in the reaction vessel was replaced with nitrogen gas. Then, the mixture was heated to 50°C while stirring under a nitrogen atmosphere to start the reaction. The reaction solution was then reacted at 50°C for 4 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain a copolymer (R9) solution with a non-volatile content of 30%. The mass average molecular weight of the obtained copolymer (R9) was 890,000.
[0079] (Acrylic copolymer (R10-R11, R35-R62) Acrylic copolymers (R10 to R11, R35 to R62) were produced in the same manner as in the production of the acrylic copolymer (R9), except that the compositions and blending amounts (parts by mass) were changed to those shown in Table 1.
[0080] Tables 1, 2 and 3 show the compositions, amounts (non-volatile mass parts) and mass average molecular weights (Mw) of the obtained acrylic copolymers (R9 to R11, R35 to R62).
[0081] [Table 1]
[0082] [Table 2]
[0083] [Table 3]
[0084] The abbreviations in the table are as follows. MA: Methyl acrylate (alkyl group carbon number 1) EA: Ethyl acrylate (alkyl group carbon number: 2) 2EHA: 2-ethylhexyl acrylate (alkyl group carbon number: 8) BA: Butyl acrylate (alkyl group carbon number: 4) DOA: Dodecyl acrylate (alkyl group carbon number: 12) IBXA: Isobornyl acrylate (alkyl group (ring structure) with 10 carbon atoms) TDA: Tridecyl acrylate (alkyl group carbon number: 13) IBXMA: Isobornyl methacrylate (alkyl group (ring structure) with 10 carbon atoms) nHA: n-heptyl acrylate (alkyl group carbon number 7) IAA: Isoamyl acrylate (alkyl group (branched) with 5 carbon atoms) 4HBA: 4-hydroxybutyl acrylate 2HEA: 2-hydroxyethyl acrylate AA: Acrylic acid DMAEA: 2-Dimethylaminoethyl acrylate ACMO: acryloylmorpholine MDEA: methoxydiethylene glycol acrylate a1: (meth)acrylic acid alkyl ester monomer having an alkyl group with 1 to 3 carbon atoms a2: (meth)acrylic acid alkyl ester monomer with an alkyl group having 4 or more carbon atoms a3: hydroxyl group-containing monomer A4: Acid-containing monomer a5: Amino group-containing monomer a6: amide group-containing monomer a7: Oxyalkylene group-containing monomer
[0085] Example 1 <Preparation of Adhesive> To 100 parts of the nonvolatile content of the acrylic copolymer (R9), 0.14 parts of the hexamethylene diisocyanate-trimethylolpropane adduct D-160N as a curing agent and 0.1 parts of KBM-403 as a low-polarity additive were added, and ethyl acetate was further added so that the nonvolatile content became 20%, and the mixture was stirred to obtain an adhesive.
[0086] <Preparation of adhesive sheet> The adhesive was applied to a 75 μm thick polyethylene terephthalate separator (release film 1) so that the thickness after drying would be 50 μm, and an adhesive layer was formed by drying with hot air at 100° C. for 2 minutes. Next, a 50 μm thick polyethylene terephthalate separator (release film 2) was bonded to this adhesive layer to obtain a first adhesive sheet.
[0087] <Preparation of Laminate> One of the separators was peeled off from the adhesive sheet, and the exposed adhesive layer was attached to a light-transmitting flexible substrate, CPI (colorless polyimide, manufactured by KOLON, 50 μm, polar term component 4.5 mN / m), using a laminator in an atmosphere of 25° C. and 50% relative humidity. The other separator was peeled off, and the resulting layer was attached to a 188 μm-thick PET film using a laminator to obtain a laminate of PET film / adhesive layer / light-transmitting flexible substrate.
[0088] (Examples 2 to 40, Comparative Examples 1 to 12) Pressure-sensitive adhesive sheets were obtained in the same manner as in Example 1, except that the types and amounts (parts by mass) of the acrylic copolymer, curing agent, and additives were changed as shown in Tables 4 to 7. Then, the pressure-sensitive adhesive layer was attached to the light-transmitting flexible substrate shown in Tables 4 to 7 to obtain a laminate of PET film / pressure-sensitive adhesive layer / light-transmitting flexible substrate.
[0089] Evaluation of the adhesive layer The physical properties of the pressure-sensitive adhesive layer and the laminate were measured and evaluated by the following methods. The results are shown in Tables 4 to 7.
[0090] <Measurement of the mass (coating amount) per unit area of adhesive layer> The obtained adhesive sheet was cut to a size of 100 mm x 100 mm, and the mass was measured (mass W (g)). Separately, a 75 μm thick polyethylene terephthalate separator (release film 1) and a 50 μm thick polyethylene terephthalate separator (release film 2) used in the adhesive sheet were each cut to a size of 100 mm x 100 mm, and the mass was measured (mass W75 (g) and mass W50 (g), respectively). Coating amount (g / m 2 )=(W-W75-W50) / 0.01
[0091] <Measurement of gel fraction> The obtained adhesive sheet was cut into a size of 30 mm x 100 mm, and the 50 μm thick polyethylene terephthalate separator (release film 2) was peeled off to expose the adhesive layer, which was attached to a weighed 300 mesh stainless steel wire net (mass W0), and the 75 μm thick polyethylene terephthalate separator (release film 1) was peeled off to obtain a sample. The weight of the sample was W1, and the sample was left in ethyl acetate for 24 hours, dried at 100°C for 1 hour, and weighed to obtain W2, which was calculated using the following formula. Gel fraction (%) = {(W2-W0) / (W1-W0)} x 100
[0092] <Measurement of polar term components of surface free energy> The 50 μm thick polyethylene terephthalate separator (release film 2) was peeled off from the obtained pressure-sensitive adhesive sheet to expose the pressure-sensitive adhesive layer, which was then measured. For the measurements, a KRUSS MSA was used, and the polarity term was calculated using the OWRK method from the contact angle 1 second after 1 μl each of water and diiodomethane landed on the adhesive layer or the light-transmitting flexible substrate.
[0093] <Evaluation of whitening at bent parts, edge misalignment, and edge protrusion using standard bending test> Using the obtained laminate, a normal condition test was performed using a bending tester (manufactured by Yuasa System Co., Ltd.) in an atmosphere of 25°C and relative humidity of 50%, with the inner diameter when bent set to 3 mm. One cycle consisted of bending and opening by 180°, and the test was repeated 300,000 times at a pace of 30 reciprocations per minute. After the test, the appearance was evaluated for whitening at the bent portion and misalignment of the edge of the adherend according to the following criteria. The higher the evaluation value, the better the product. A score of 3 or higher indicates practical use. Appearance: The test laminate was visually inspected for the presence or absence of air bubbles, misalignment of the edges of the adherends, and protrusion of the edges of the pressure-sensitive adhesive layer under the following conditions.
[0094] [Whitening of bends] 5: No air bubbles are observed within 5 mm on either side of the bend. 4: There are 1 to 10 air bubbles within 5 mm on each side of the bend. 3: There are 11 to 50 air bubbles within a 5 mm radius on each side of the bend. 2: There are 51 to 100 air bubbles within a 5 mm radius on each side of the bend. 1: There are 100 or more air bubbles within 5 mm on each side of the bend.
[0095] [Edge misalignment] 5: The misalignment between the PET film and the light-transmitting flexible substrate is less than 1 mm. 4: The misalignment between the PET film and the light-transmitting flexible substrate is 1 mm or more and less than 2 mm. 3: The misalignment between the PET film and the light-transmitting flexible substrate is 2 mm or more and less than 3 mm. 2: The misalignment between the PET film and the light-transmitting flexible substrate is 3 mm or more and less than 4 mm. 1: The misalignment between the PET film and the light-transmitting flexible substrate is 4 mm or more.
[0096] [End overhang] 5: The adhesive layer protrudes from the edge of the adhesive layer by less than 100 μm. 4: The adhesive layer protrudes from the edge of the adhesive layer by 100 μm or more and less than 200 μm. 3: The adhesive layer protrudes from the edge of the adhesive layer by 200 μm or more and less than 300 μm. 2: The adhesive layer protrudes from the edge of the adhesive layer by 300 μm or more and less than 400 μm. 1: The adhesive layer protrudes from the edge of the tape by 400 μm or more.
[0097] <Evaluation of whitening of bent parts, edge misalignment, and edge protrusion due to high-speed bending test> The standard bending test was conducted with a reciprocating pace of 120 reciprocations per minute and 100,000 cycles, and was evaluated using the same evaluation criteria as the standard bending test.
[0098] [Table 4]
[0099] [Table 5]
[0100] [Table 6]
[0101] [Table 7]
[0102] The abbreviations in the table are as follows. <Hardening agent> D-110N: Trimethylolpropane adduct of xylylene diisocyanate D-160N: Hexamethylene diisocyanate trimethylolpropane adduct EX-313: Multifunctional epoxy compound (glycerol polyglycidyl ether) D-370N: Isocyanurate of 1,5-pentamethylene diisocyanate DID: Decamethylene diisocyanate trimethylolpropane adduct <Additives> KBM-403: Epoxy silane KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd. KBE-403: Epoxy silane KBE-403 manufactured by Shin-Etsu Chemical Co., Ltd. KBM-303: Epoxy silane KBM-303 manufactured by Shin-Etsu Chemical Co., Ltd. BYK-325N: BYK-Chemie Japan Co., Ltd. Silicon-containing surface conditioner BYK-325N 390S: Chlorinated polyolefin 390S manufactured by Nippon Paper Industries Co., Ltd. BX: Chlorinated EVA BX manufactured by Nippon Paper Industries Co., Ltd.
[0103] <Light-transmitting flexible base material> CPI: Colorless polyimide (KOLON, 50 μm, polar component 4.5 mN / m) P-CPI: Plasma-treated colorless polyimide (treated with the above CPI, 50 μm, polar term component 7.6 mN / m) PET: Polyethylene terephthalate (Toyobo Co., Ltd., 50 μm, polar component 5.8 mN / m) PMMA: Polymethyl methacrylate (Mitsubishi Chemical Corporation, 53 μm, polar component 6.8 mN / m) C-HDPE: High density polyethylene (NT Film Co., Ltd., 50 μm) corona treated (polar term component 4.8 mN / m) C-OPP: Oriented polypropylene (Toyobo Co., Ltd., 40 μm) corona treated (polar term component 4.6 mN / m)
[0104] Corona treatment for producing C-HDPE and C-OPP was performed using a corona treatment device Plasmadyne manufactured by Navitas, with the corona discharge nozzle swept once from one end of the substrate to the other at a speed of 100 mm / sec and a distance of 20 mm between the corona discharge nozzle and the substrate.
[0105] From the results of Tables 4 to 7, the adhesive layer of the present disclosure did not cause misalignment between the adherends even when repeatedly bent, and the adhesive layer did not protrude from the edge. In addition, even when a colorless polyimide was used as the light-transmitting flexible substrate, it was confirmed that the bent portion did not whiten due to foaming. As a result, a display including a laminate having the adhesive layer of the present disclosure has excellent flexibility, and therefore a display with excellent visibility can be obtained. On the other hand, the pressure-sensitive adhesive layers of Comparative Examples 1 to 12 could not satisfy all of the above properties. [Explanation of symbols]
[0106] 1 First adhesive layer 3. Light-transmitting flexible substrate (cover panel) 4. Polarizing Plate 5 Second adhesive layer 6 Barrier Layer 7 Organic EL layer 8 Support 9 Organic EL Cell
Claims
1. A laminate for flexible displays comprising a pressure-sensitive adhesive layer on a light-transmitting flexible substrate, the polar term component of the surface free energy of the light-transmitting flexible substrate calculated based on the OWRK method from the contact angle of water and the contact angle of diiodomethane is 3.0 mN / m or more; the polar term component of the surface free energy of the pressure-sensitive adhesive layer calculated based on the OWRK method from the contact angle of water and the contact angle of diiodomethane is 0.5 mN / m or less; The pressure-sensitive adhesive layer has a mass per unit area of 10 to 100 g / m 2 and the pressure-sensitive adhesive layer is formed from an acrylic pressure-sensitive adhesive, The acrylic pressure-sensitive adhesive is an acrylic copolymer containing, based on 100% by mass of the acrylic copolymer, 25% by mass or less of repeating units derived from hydroxyl group-containing monomers, 10% by mass or less of repeating units derived from acid-containing monomers, 15% by mass or less of repeating units derived from amide group-containing monomers, 15% by mass or less of repeating units derived from amino group-containing monomers, and 75 to 90% by mass of repeating units derived from (meth)acrylic acid alkyl esters in which the alkyl group has 4 or more carbon atoms, and a low-polarity additive.
2. 2. The laminate for flexible displays according to claim 1, wherein the polar term component of the surface free energy of the pressure-sensitive adhesive layer calculated based on the OWRK method from the contact angle of water and the contact angle of diiodomethane is 0.2 mN / m or less.
3. The pressure-sensitive adhesive layer has a mass per unit area of 25 to 70 g / m 2 and the pressure-sensitive adhesive layer has a gel fraction of 60 to 80 mass %.
4. 2. The laminate for flexible displays according to claim 1, further comprising 0.02 to 4.0 parts by mass of a curing agent based on 100 parts by mass of the acrylic copolymer.
5. The laminate for flexible displays according to any one of claims 1 to 4, further comprising a polarizing plate on the pressure-sensitive adhesive layer.
6. A flexible display comprising the laminate according to claim 5 and an optical element.
Citation Information
Patent Citations
Adhesive resin composition, adhesive resin cured product, adhesive sheet, and image display device laminate
JP2020097737A
Optically transparent adhesive sheet, composition for manufacturing the same, and flat panel display device using the same
JP2020517800A